Arrhenius-based shelf-life prediction of lombok terong (Capsicum) sambal with sodium benzoate and potassium sorbate combination - Eileen Fiona Wijaya; Fransisca Romana Titis Suniati; Oki Krisbianto; Evelyn Goeyana; Ika Yohanna Pratiwi (AGROINTEK, 2026)
Lombok terong is a variety of chili belonging to the Capsicum genus, and one of its processed products is sambal sauce. Due to its limited shelf life, preservatives must be used to extend it. This study utilized a combination of sodium benzoate and potassium sorbate in a 1:1 ratio. The objective was to identify suitable indicators of quality degradation and critical parameters for predicting the shelf life of lombok terong sambal sauce (LTSS), and to develop a predictive model based on the Accelerated Shelf-Life Testing (ASLT) method using the Arrhenius approach. The study tested samples over 30 days, with observations made every six days. The samples were stored at temperatures of 30℃ (S30), 40℃ (S40), and 50℃ (S50), with two replicates per treatment, and each replicate measured in triplicate. Indicators of quality degradation included color analysis and Total Plate Count (TPC), while water content, water activity, and pH analysis were critical parameters. Based on the experimental results, TPC analysis was selected as the indicator of quality degradation, as significant microbial growth was observed in the sample stored at 50℃ by day 18. Meanwhile, pH analysis was identified as the critical parameter due to significant decreases observed across all storage conditions. As a result, the estimated shelf-life equation for lombok terong sambal sauce can be formulated as t = pH0 - 4.4 × e3612T1642.542.